Manufacturing method of iron-based soft magnetic alloy
The iron-based soft magnetic alloy manufacturing method addresses the limitations of FE-Si-B alloys by achieving 1.7T saturation magnetic flux density and low iron loss, suitable for BLDC motors, through a rapid cooling process with specific alloy composition and cooling roll design.
Patent Information
- Application Number
- JP2024168474
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-03
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Existing FE-Si-B amorphous alloys struggle to achieve a saturation magnetic flux density of 1.7T or higher while maintaining low iron loss, making them unsuitable for high-torque applications in BLDC motors, and are difficult to process into laminated cores due to brittleness and thickness limitations.
A manufacturing method for an iron-based soft magnetic alloy with a composition formula (FE1-mCo m)100-x-ySi x(B1-nC n)y, involving rapid cooling on a cooling roll with specific dimensions and surface roughness, using a nozzle to produce ultra-fine α-Fe crystals, ensuring a high saturation magnetic flux density and low iron loss.
The method enables the production of an iron-based soft magnetic alloy with a saturation magnetic flux density of 1.7T or higher and low iron loss, suitable for BLDC motors, while maintaining a high core accumulation ratio for laminated cores.
Smart Images

Figure 0007625198000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an iron-based soft magnetic alloy, and more particularly to a method for producing an iron-based soft magnetic alloy applicable to various brushless DC motors. [Background technology]
[0002] In recent years, there has been a demand from the market for materials with low iron loss and high saturation magnetic flux density for various passive elements and transformers in the power electronics field, such as inductors and reactors used as electronic components. There is an increasing demand for iron-based amorphous materials, which are soft magnetic materials with high magnetic permeability and low iron loss, and Fe-Si-B rapidly solidified alloy thin ribbons with a thickness of approximately 17 μm to 25 μm, which are produced by rapid solidification of a molten metal made primarily of iron (Fe), silicon (Si), and boron (B), such as iron-based nanocrystalline materials, as low iron loss soft magnetic materials to replace conventional silicon steel sheets (Fe-Si), for use in large transformers and inductors.
[0003] In addition, the Fe-Si-B-based rapidly solidified alloys have been considered for use in the stator cores of brushless direct current (BLDC) motors, taking advantage of their low iron loss compared to silicon steel sheets, and for the purpose of reducing the iron loss in the stator cores and increasing the efficiency of brushless direct current (BLDC) motors. In particular, in high-speed motors that exceed 10,000 rpm or 20,000 rpm, the operating range of soft magnetic materials is a high-frequency band of 1 kHz or more, so it has been confirmed that the iron loss in the stator cores is suppressed and unprecedented high efficiency can be achieved. Furthermore, in the current situation where about 60% of the world's electricity is consumed by motors, increasing the efficiency of motors is expected to be a direct means of achieving carbon-free society, and it is expected that this will be used in electric vehicles, white goods such as air conditioners, and motors for factory automation.
[0004] However, the above Fe-Si-B amorphous alloy has a saturation magnetic flux density of 1.6 T or less, which is lower than the 1.8 T of electromagnetic steel sheets, which are currently used as motor core materials, and so while it can ensure the necessary motor output in high-speed motors of 10,000 rpm or more, it is difficult to apply it to motors that require high torque from low rotation speeds, such as factory automation and air mobility. For this reason, there is a demand for an iron-based soft magnetic material that can achieve both low iron loss performance comparable to that of Fe-Si-B amorphous alloys while ensuring a high saturation magnetic flux density of about 1.8 T, which is comparable to that of electromagnetic steel sheets.
[0005] Due to the above market demands, it is difficult for Fe-Si-B based amorphous alloys, which have a maximum Bs of around 1.6 T, or iron-based nanocrystalline materials (such as FINEMET (registered trademark)), which have a Bs of around 1.4 T, to replace electromagnetic steel sheets with a Bs of 1.8 T. To date, there have been no examples of BLDC motors using Fe-Si-B based rapidly solidified alloys being brought to the market as motors for factory automation or air mobility.
[0006] Until now, BLDC motors for the above-mentioned factory automation and air mobility have combined magnetic steel sheet core materials with anisotropic rare earth iron boron sintered magnets, which exhibit excellent permanent magnetic properties, to achieve high efficiency by utilizing magnet torque. However, with magnetic steel sheets, which have high iron loss, the input power is lost through iron loss generated in the stator core, making it impossible to obtain the motor efficiency required for BLDC motors for factory automation and air mobility. Therefore, there is extremely high market demand for high-output, high-efficiency BLDC motors that can contribute to energy savings in a variety of applications.
[0007] Furthermore, Fe-Si-B amorphous alloys can significantly reduce iron loss to less than one-tenth that of electromagnetic steel sheets, and because they also have high magnetic permeability, if they can overcome the issue of lower Bs than electromagnetic steel sheets, then it will be possible to ensure the motor output required for BLDC motors for factory automation and air mobility by achieving Bs ≥ 1.7 T. For this reason, there are extremely high expectations worldwide from the motor market for core materials that achieve low iron loss on a par with iron-based amorphous alloys that can achieve Bs ≥ 1.7 T, making them an alternative to electromagnetic steel sheets.
[0008] The electromagnetic steel sheets used in the rotor cores and stator cores of BLDC motors are used as laminated cores, but existing Fe-Si-B amorphous alloys are difficult to punch due to their thin thickness of about 20 μm. In addition, because the alloy is thin, the space factor when made into a laminated core is low (less than 90%) compared to the 92% or more of electromagnetic steel sheets, due to the thin alloy thickness. This makes it difficult to obtain motor torque on a par with that of electromagnetic steel sheets.
[0009] In Non-Patent Document 1, it is stated that Fe-Si-B amorphous alloys have been 4 ~10 6 It has been disclosed that an amorphous structure can be obtained only when the rapidly solidified alloy ribbon has a thickness of about 17 to 22 μm and is rapidly solidified at an extremely fast rapid solidification rate of, for example, 100,000 sec., but that it is possible to obtain an iron-based amorphous alloy ribbon with a thickness of 50 μm or more by slowing down the rapid solidification rate by adding phosphorus (P). However, not only does the addition of P cause a decrease in the saturation magnetic flux density Bs, but in the case of P-added alloys, the P component volatilizes during alloy melting, causing significant contamination inside the furnace, and therefore there are still few examples of its application in the industrial field.
[0010] Non-Patent Document 2 discloses that the Fe-Si-B-P-Cu system iron-based nanocrystalline alloy "NANOMET (registered trademark)" is a soft magnetic material that has a high saturation magnetic flux density Bs: 1.85 T and low iron loss performance comparable to that of an iron-based amorphous alloy. However, this iron-based nanocrystalline alloy is very brittle and difficult to form into a laminated core by punching and pressing, making it difficult to apply to the rotor core and stator core of a BLDC motor at the mass-production level, and except for at the prototype level, there have been no examples of it being used practically as a core material for a motor.
[0011] Patent Documents 1, 2, and 3 describe methods for producing rapidly solidified alloy ribbons with a thickness of 50 μm or more. However, none of them have produced an Fe-Si-B-based amorphous alloy with Bs ≧ 1.7 T that is intended for application to laminated cores for BLDC motors for driving EVs, and there are no examples yet of industrial use of iron-based amorphous alloys as soft magnetic materials to replace silicon steel sheets.
[0012] Patent Document 4 discloses a method for producing a metal ribbon, characterized in that molten metal is ejected from a plurality of openings (multi-hole nozzles) arranged on a moving cooling substrate (rotating cooling roll) at a substantially right angle to the direction of movement of the substrate and each of which has an angle of 10 to 80° to the direction of movement, and then rapidly cooled and solidified. However, Patent Document 4 is an invention made for the purpose of reducing the variation in thickness of a metal ribbon in the width direction when producing a wide rapidly cooled ribbon. In addition, it is difficult to process a plurality of openings having an elongated parallelogram, trapezoid, or ellipse shape with angles of 10 to 80°, and there is also a problem of high nozzle processing costs, making it difficult to use on an industrial mass production level.
[0013] Patent Document 5 discloses a method for producing an Fe-Si-B based amorphous alloy having a thickness of 40 μm or more, but does not disclose an alloy composition that can ensure Bs≧1.7 T, and does not aim to provide a soft magnetic material for BLDC motors for driving EVs.
[0014] Patent Document 6 describes an Fe-Si-B based rapidly solidified alloy having a thickness of 40 μm to 70 μm and a saturation magnetic flux density Bs≧1.7 T and a coercive force Hc≦200 A / m, and a method for producing the same. However, during the rapid solidification process, 0.1 vol % to 10 vol % of an α-Fe phase precipitates in the surface layer, and the remainder of the rapidly solidified alloy is an amorphous structure. This may make it difficult to perform punching press processing depending on the core shape. [Prior art documents] [Patent documents]
[0015] [Patent Document 1] Patent Publication No. 5-329587 [Patent Document 2] JP 7-113151 [Patent Document 3] Patent Publication No. 8-124731 [Patent Document 4] Patent Publication No. 63-220950 [Patent Document 5] Patent Publication No. 2018-153828 [Patent Document 6] Patent Publication No. 2021-193199 [Non-patent literature]
[0016] [Non-Patent Document 1] Creation of new bulk metallic glass / amorphous thick plates with high saturation magnetic flux density (Tohoku University, Metallic Glass Research Center) Akihiro Makino, Ken Kubota, Tono Chuntao [Non-Patent Document 2] Latest research and development trends of ultra-low core loss, high iron content soft magnetic alloy "NANOMET", Journal of the Japan Society for Metals Material, Vol. 55, No. 3 (2016) Summary of the Invention [Problem to be solved by the invention]
[0017] It is hoped that an Fe-Si-B rapidly solidified alloy with Bs ≧ 1.7T equivalent to that of electromagnetic steel sheets, which are widely used for transformers and various motors, will be developed that has low core loss performance comparable to that of Fe-Si-B amorphous alloys, which can achieve significant improvements in motor efficiency while maintaining a saturation magnetic flux density at the same level as electromagnetic steel sheets, and can be stamped using a press like electromagnetic steel sheets, can maintain a core space factor of 90% or more, and can be used as laminated cores for various motors. In order to maintain Bs ≧ 1.7T, it is necessary to reduce the composition ratios of boron (B) and silicon (Si) in the alloy composition in order to increase the volume ratio of the α-Fe phase. However, when the B+Si ratio is lowered, the amorphous formation ability of the Fe-Si-B alloy drops significantly, and coarse α-Fe is generated non-uniformly during rapid solidification. This makes it impossible to obtain low iron loss performance comparable to that of Fe-Si-B amorphous alloys. Therefore, even if the B+Si ratio is lowered, it is difficult to ensure a rapid solidification rate at which coarse α-Fe is not generated non-uniformly during rapid solidification.
[0018] Therefore, an object of the present invention is to provide a method for producing an iron-based soft magnetic alloy that can produce an Fe-Si-B based rapidly solidified alloy having a high Bs of Bs≧1.7 T and low iron loss performance comparable to that of an Fe-Si-B based amorphous alloy. [Means for solving the problem]
[0019] The method for producing an iron-based soft magnetic alloy according to the present invention comprises the steps of: 1-m Co m ) 100-x-y S x (B 1-n C n ) y and a rapid solidification step of rapidly solidifying the molten alloy sprayed from a nozzle onto a chill roll made of pure copper, a copper alloy, Mo, or W as a main raw material, the chill roll having an outer diameter of 300 mm or more and 2000 mm or less, a cylindrical cooling water passage through which cooling water flows in the axial direction is formed inside the chill roll, the arithmetic mean roughness (Ra) of the surface is 0.01 μm or more and 0.6 μm or less, and the radial thickness from the surface to the cooling water passage is 5 mm or more and less than 25 mm, and the rapid solidification step includes a ... 3 / min or more 20m 3 The method includes a step of spraying the molten alloy from the nozzle onto the surface of the chill roll, through which water is passed at a flow rate of less than 1 / min, while rotating the chill roll at a roll surface speed of 15 m / sec to 50 m / sec, thereby forming a ribbon-shaped rapidly solidified alloy having a thickness of 18 μm to 40 μm and consisting mainly of ultrafine α-Fe with an average crystal grain size of 1 nm or less.
[0020] In the manufacturing method of this iron-based soft magnetic alloy, the nozzle is preferably made of a material mainly composed of any one of quartz (SiO2), boron nitride (BN), silicon carbide (SiC) and alumina (Al2O3), and the molten alloy is preferably sprayed at a pressure of 5 kPa or more and 50 kPa or less.
[0021] It is preferable that the nozzle is a single slit nozzle and is arranged so that the longitudinal direction of the slit is perpendicular to the rotation direction of the cooling roll, the opening width of the slit is 0.2 mm or more and 0.8 mm or less, and the distance from the nozzle to the cooling roll is 0.1 mm or more and 2.0 mm or less. Effect of the Invention
[0022] According to the present invention, it is possible to provide a method for producing an iron-based soft magnetic alloy that can produce an Fe-Si-B based rapidly solidified alloy having a high Bs of Bs≧1.7 T and low core loss performance comparable to that of an Fe-Si-B based amorphous alloy. [Brief description of the drawings]
[0023] [Figure 1] 1(a) is a schematic diagram of a manufacturing apparatus used in a method for manufacturing an iron-based soft magnetic alloy according to one embodiment of the present invention, (b) is an enlarged view of a main part thereof, and (c) is an enlarged view of the bottom surface of a nozzle. [Diagram 2] 2A is a longitudinal sectional view of a cooling roll of the manufacturing apparatus shown in FIG. 1, and FIG. 2B is a sectional view taken along the line AA of FIG. [Diagram 3] 1 is a powder X-ray diffraction profile of the iron-based soft magnetic alloy obtained in Example 3. [Figure 4] 1 is a powder X-ray diffraction profile of the iron-based soft magnetic alloy obtained in Example 6. [Diagram 5] 1 shows an X-ray powder diffraction profile of the iron-based soft magnetic alloy obtained in Comparative Example 9. [Figure 6] 1 shows an X-ray powder diffraction profile of the iron-based soft magnetic alloy obtained in Comparative Example 11. [Figure 7] 3 is a transmission electron microscope (TEM) photograph of the iron-based soft magnetic alloy of Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The method for producing an iron-based soft magnetic alloy of the present invention can produce an Fe-Si-B based rapidly solidified alloy that has low iron loss performance equal to or greater than that of Fe-Si-B based amorphous alloys, with iron loss less than 1 / 10 that of electromagnetic steel sheet, while ensuring a saturation magnetic flux density Bs ≧ 1.7 T that is suitable for use in BLDC motors for factory automation and air mobility, by making ultrafine α-Fe of 1 nm or less the main phase in the rapid solidification process during production.
[0025] [Alloy composition] By using Fe as an essential element to account for the remainder of the above elements and substituting a portion of Fe with Co, which is a ferromagnetic element like Fe, Bs≧1.7T can be ensured. However, if the substitution rate m of Co for Fe is less than 5%, Bs≧1.7T cannot be ensured. Furthermore, if the substitution rate m of Co for Fe exceeds 50%, Bs tends to decrease. For this reason, the substitution rate m of Co for Fe is limited to 5% or more and 50% or less. The substitution rate m is preferably 10% or more and 40% or less, and more preferably 15% or more and 35% or less from the viewpoint of cost-effectiveness.
[0026] In the iron-based soft magnetic alloy obtained by the present invention, Si is not only an essential element for obtaining a fine structure, but also plays an important role in expressing soft magnetic properties such as magnetic permeability. If the composition ratio x of Si is less than 1.0 atomic %, not only the magnetic permeability at an applied magnetic field of 10 A / m deteriorates to 2000 or less, but also the core loss (core loss) at 1 kHz and 1.5 T becomes 100 W / kg or more, so that the characteristics of the iron-based soft magnetic alloy of the present invention, that is, high magnetic permeability and low core loss, are reduced compared to electromagnetic steel sheets. Furthermore, if the composition ratio x of Si exceeds 3.0 atomic %, the abundance ratio of Fe, which is responsible for magnetization, decreases and Bs≧1.7T cannot be obtained. For this reason, the composition ratio x of Si is 1.0 atomic % or more and 3.0 atomic % or less. The composition ratio x of Si is preferably 1.2 atomic % or more and 2.5 atomic % or less, and more preferably 1.3 atomic % or more and 2.2 atomic % or less.
[0027] If the composition ratio y of B+C is less than 11.0 atomic %, the metal structure of the iron-based soft magnetic alloy obtained by quenching the molten metal becomes coarse, and not only is it not possible to ensure low iron loss performance of 50 W / kg or less at a magnetic flux density of 1.5 T and a frequency of 1 kHz, but also the iron-based soft magnetic alloy is prone to cracking during the punching process by pressing, making it difficult to form a laminated core. Also, if the composition ratio y of B+C exceeds 14.0 atomic %, the abundance ratio of Fe, which is responsible for magnetization, decreases and Bs≧1.7 T cannot be obtained. For this reason, the composition ratio y of B+C is 11.0 atomic % or more and 14.0 atomic % or less. The composition ratio y of B+C is preferably 11.5 atomic % or more and 13.5 atomic % or less, and more preferably 12.0 atomic % or more and 13.5 atomic % or less.
[0028] By replacing a portion of B with C, the melting point of the molten alloy is lowered, the conditions for quenching the molten alloy are relaxed, and it becomes easier to produce an Fe-Si-B based rapidly solidified alloy by the manufacturing method of the present invention. However, if the substitution ratio n of C to B exceeds 30%, it is not preferable because Bs≧1.7T cannot be ensured. For this reason, the substitution ratio n is limited to 30% or less. From the viewpoint of achieving both high Bs characteristics and low magnetic permeability, the substitution ratio n is preferably 20% or less, and more preferably 15% or less.
[0029] In the iron-based soft magnetic alloy (Fe-Si-B type rapidly solidified alloy) obtained by the present invention, it is possible to add one or more additive elements selected from the group consisting of Al, Si, V, Ti, Mn, Zn, Ga, Zr, Nb, Mo, Ag, Hf, Ta, W, Pt, Au and Pb, but if the added concentration exceeds 2.0 atomic %, Bs≧1.7T cannot be obtained, so it is not preferable, and it is acceptable if it is within 2.0 atomic %, including the mixture as an impurity. Note that Cu is not solid-soluble in Fe, which is the main raw material, and if Cu is added, Cu dispersed in the ultrafine α-Fe structure will precipitate alone, which may hinder the formation of the desired alloy structure, so the iron-based soft magnetic alloy of the present invention does not contain Cu.
[0030] [Metal structure] The iron-based soft magnetic alloy obtained by the present invention is characterized in that the main phase is α-Fe, which is isotropically precipitated without being oriented in a specific direction. The main phase is the phase with the largest volume ratio, and the volume ratio is preferably 50% or more, and more preferably 80% or more. The isotropically precipitated α-Fe crystal phase is an ultrafine crystal with an average crystal grain size of 1 nm or less. The average crystal grain size of the α-Fe phase can be determined by the half-width of the X-ray diffraction peak by powder X-ray diffraction (XRD) described later, or by transmission electron microscope (TEM).
[0031] However, even if an amorphous phase is present in the metal structure of the iron-based soft magnetic alloy obtained when the molten alloy is rapidly solidified on a rotating cooling roll, it is acceptable as long as the amount does not adversely affect the soft magnetic properties. If the amorphous phase in the metal structure of the iron-based soft magnetic alloy exceeds 20 volume % of the entire metal structure, it becomes difficult to achieve Bs≧1.7T, so the content of the amorphous phase is 20 volume % or less. The content of the amorphous phase is preferably 10 volume % or less, and more preferably 5.0 volume % or less.
[0032] [Magnetic properties] The saturation magnetic flux density Bs of the iron-based soft magnetic alloy obtained by the present invention is 1.7 T or more and 2.0 T or less in the state immediately after rapid solidification (as-spun) or after heat treatment at a temperature of 180 ° C or more and less than 450 ° C for the purpose of removing distortion from the as-spun state. If Bs exceeds 2.0 T, the iron loss at a magnetic flux density of 1.5 T and a frequency of 1 kHz exceeds 50 W / kg, so that when applied to a core for a BLDC motor for FA and air mobility, etc., a clear improvement in motor efficiency is not obtained compared to a core made of electromagnetic steel sheet. From the viewpoint of achieving both a necessary and sufficient motor torque and high efficiency in the low rotation speed range, Bs is 1.7 T or more and 2.0 T or less, preferably 1.73 T or more and 1.97 T, and more preferably 1.75 T or more and 1.95 T or less.
[0033] In addition, while the iron loss value of existing magnetic steel sheets, iron-based amorphous alloys, and iron-based nanocrystalline alloys shows a tendency to increase with increasing magnetic flux density at each operating frequency, the iron-based soft magnetic alloy of the present invention shows a very unique magnetic property in that the iron loss value of each operating frequency shows a clear tendency to saturate with increasing magnetic flux density. In particular, the iron loss value at a magnetic flux density of 1.5T at a frequency of 20kHz, which is a high frequency range, is 1500W / kg or less, and there is a possibility that the iron loss that is a problem in ultra-high speed rotating motors of 50,000 rpm or more and transformers of voltage step-up units can be significantly reduced. If the iron loss value at a magnetic flux density of 1.5T at a frequency of 20kHz is too high (for example, 2000W / kg or more), the iron loss will be at the same level as that of iron-based amorphous alloys and iron-based nanocrystalline alloys, so the iron loss value at a magnetic flux density of 1.5T at a frequency of 20kHz is preferably 1500W / kg or less, more preferably 1300W / kg or less, and even more preferably 1000W / kg or less.
[0034] [Method of manufacturing iron-based crystalline alloy] The method for producing an iron-based crystalline alloy of the present invention includes a step of preparing a molten alloy having the above-mentioned composition, and a step of rapidly solidifying the prepared molten alloy by rapidly cooling.
[0035] Fig. 1(a) is a schematic diagram of a single-roll molten metal quenching apparatus used in a method for producing an iron-based soft magnetic alloy according to an embodiment of the present invention, Fig. 1(b) is an enlarged view of a nozzle, and Fig. 1(c) is an enlarged view of the nozzle bottom. The single-roll molten metal quenching apparatus 1 shown in Fig. 1 includes a melting furnace 2, a molten metal storage vessel 5, and a cooling roll 8.
[0036] The melting furnace 2 supplies the molten alloy 3, obtained by melting the raw materials by high-frequency induction heating, to a molten alloy storage container 5 by rotating a tilting shaft 4. The molten alloy storage container 5 is provided with a nozzle 6 at its bottom, and the molten alloy 3 is further heated by a heating coil (not shown) and ejected from a slit 7 formed at the lower end of the nozzle 6 onto the surface (outer circumferential surface) of a cooling roll 8. The cooling roll 8 quenches the molten alloy in contact with its surface by supplying cooling water thereinto, forming a ribbon-like rapidly solidified alloy 9. The material of the nozzle 6 can be appropriately selected from those mainly composed of, for example, quartz (SiO2), boron nitride (BN), silicon carbide (SiC), and alumina (Al2O3).
[0037] The nozzle 6 is a single slit nozzle in which a single slit 7 is formed, and the longitudinal direction of the slit 7 is arranged so as to be perpendicular to the rotation direction of the chill roll 8 (i.e., parallel to the rotation axis of the chill roll 8). The width W1 of the slit 7 plays a role in adjusting the rate of discharge of the molten alloy 3 supplied to the chill roll 8. If the slit width W1 is too small, slit processing is likely to become difficult, and furthermore, the slit 7 is likely to be blocked by the molten alloy. On the other hand, if the slit width W1 is too large, the discharge rate becomes too high, and the heat removal by the chill roll 8 is not kept up, and the rapidly solidified alloy sticks to the chill roll 8, making it difficult to continue stable molten rapid solidification. Therefore, the slit width W1 is 0.2 mm or more and 0.8 mm or less. The slit width W1 is preferably 0.3 mm or more and 0.7 mm or less, and more preferably 0.3 mm or more and 0.6 mm or less.
[0038] The nozzle 6 may be a strand nozzle in which a plurality of holes are arranged in a row perpendicular to the rotation direction of the chill roll 8 (i.e., parallel to the rotation axis of the chill roll 8) instead of the slit nozzle shown in FIG. 1(c). The diameter of each hole of the strand nozzle is 0.6 mm to 1.3 mm, preferably 0.7 mm to 1.2 mm, and more preferably 0.7 mm to 1.1 mm. If the diameter of the hole is less than 0.6 mm, the amount of molten metal discharged per hole is small, so that the temperature at the tip of the nozzle 6 decreases, and there is a risk that the molten metal cannot be continuously discharged. On the other hand, if the diameter of the hole exceeds 1.3 mm, the amount of molten metal discharged per hole becomes too large, so that the molten metal is not rapidly cooled completely, and coarse α-Fe may precipitate, which deteriorates the magnetic properties. Moreover, if the interval between the holes is too small, the molten metal coming out of each hole may come into contact with each other, leading to incomplete quenching of the molten metal and the precipitation of coarse α-Fe particles that may cause deterioration of the magnetic properties, so the interval between the holes is preferably 1.0 mm or more, more preferably 3.0 mm or more, and even more preferably 5.0 mm or more. From the viewpoints of the production efficiency of the rapidly solidified alloy and prevention of a decrease in the temperature at the nozzle tip, the interval between the holes is preferably 20 mm or less. The shape of the opening of the nozzle 6 may be other shapes, such as a single hole.
[0039] The molten metal supplied to the surface of the chill roll 8 becomes a ribbon-like rapidly solidified alloy 9 by the rotation of the chill roll 8, and is peeled off from the chill roll 8. If the surface speed of the chill roll 8 is less than 15 m / sec, the rapidly solidified alloy becomes excessively thick, 40 μm or more, and the α-Fe crystalline phase having an average crystal grain size of 100 nm or more, which is oriented in the (200) direction and precipitated by non-uniform nucleation during rapid solidification, may exceed 10.0 vol.% in the vicinity of the surface of the chill roll surface or free surface of the iron-based soft magnetic alloy ribbon, making it impossible to maintain a low iron loss level equivalent to that of an Fe-Si-B-based amorphous alloy. On the other hand, if the surface speed of the chill roll 8 exceeds 50 m / sec, the thickness of the iron-based soft magnetic alloy ribbon becomes less than 18 μm, and the molten metal quenching speed increases, causing the amorphous phase to become dominant instead of the α-Fe crystalline phase, making it difficult to ensure Bs≧1.7T. Therefore, the surface speed of the cooling roll 8 is 15 m / sec to 50 m / sec, preferably 20 m / sec to 45 m / sec, and more preferably 25 m / sec to 40 m / sec, thereby making it possible to obtain a ribbon of rapidly solidified alloy having a thickness of 18 μm to less than 40 μm.
[0040] 1(a), if the distance d from the tip of the single slit nozzle 6 to the surface of the chill roll 8 is too small, the quenched alloy may stick to the chill roll 8, making it difficult to continue stable quenching and solidification of the molten alloy 3, whereas if the distance is too large, a puddle may not be formed on the surface of the chill roll 8, making it difficult to rapidly solidify the molten alloy 3. For this reason, the distance d is 0.1 mm or more and 2.0 mm or less, preferably 0.1 mm or more and 1.5 mm or less, and more preferably 0.15 mm or more and 1.0 mm or less.
[0041] When the nozzle 6 is a strand nozzle, if the distance d from the tip of the nozzle 6 to the surface of the cooling roll 8 is too small or too large, the same problems as in the case of the single slit nozzle described above will occur. For this reason, when the nozzle 6 is a strand nozzle, the distance d is 0.5 mm or more and 30.0 mm or less, preferably 1.0 mm or more and 20.0 mm or less, and more preferably 2.0 mm or more and 10.0 mm or less.
[0042] In producing the ribbon-shaped rapidly solidified alloy 9, the adhesion of the molten alloy 3 to the outer surface of the chill roll 8 is important, but this adhesion of the molten alloy is largely dependent on the surface roughness of the chill roll 8. If the surface roughness of the chill roll 8 is too small, the molten alloy 3 will slip on the surface of the chill roll 8, making sufficient cooling difficult, whereas if the surface roughness of the chill roll 8 is too large, the quenched alloy may stick to the chill roll 8. For this reason, the arithmetic mean roughness (Ra) of the surface of the chill roll 8 is 0.01 μm or more and 0.6 μm or less, preferably 0.05 μm or more and 0.55 μm or less, and more preferably 0.1 μm or more and 0.5 μm or less.
[0043] The chill roll 8 is preferably made of a material whose main raw material is any one of pure copper, copper alloy, molybdenum (Mo) and tungsten (W), thereby providing excellent thermal conductivity and durability. The main raw material means that it accounts for 50% or more by weight. The surface of the chill roll 8 may be plated with chromium, nickel or an alloy of these, which increases the heat resistance and hardness of the surface of the chill roll 8 and suppresses melting and deterioration of the roll surface during rapid solidification.
[0044] The outer diameter of the chill roll 8 is 300 mm or more and 2000 mm or less. If the outer diameter is less than 300 mm, the maximum distance (i.e., 1 / 4 of the circumferential length of the chill roll 8) of the molten metal ejected from the nozzle 6 onto the surface of the chill roll 8 until it peels off from the chill roll 8 becomes too short, and the molten metal cannot be sufficiently quenched on the chill roll 8. As a result, in the vicinity of the surface of the chill roll or free surface of the iron-based soft magnetic alloy ribbon, the α-Fe crystal phase having an average crystal grain size of 100 nm or more oriented in the (200) direction, which is precipitated by heterogeneous nucleation during rapid solidification, may exceed 10.0 vol %, making it impossible to maintain low iron loss at the same level as that of Fe-Si-B-based amorphous alloys. On the other hand, if the outer diameter of the chill roll 8 exceeds 2000 mm, the distance the molten metal travels before being peeled off from the chill roll 8 becomes too long, causing the molten metal to be over-quenched on the chill roll 8, increasing the molten metal quenching rate and causing the amorphous phase to become dominant rather than the α-Fe crystalline phase, making it difficult to ensure Bs ≧ 1.7 T. The outer diameter of the chill roll 8 is preferably 500 mm or more and 2000 mm or less, and taking into consideration the manufacturing cost of the chill roll 8, more preferably 500 mm or more and 1600 mm or less.
[0045] Fig. 2(a) is a longitudinal sectional view of the cooling roll 8, and Fig. 2(b) is a sectional view taken along line AA of Fig. 2(a). As shown in Fig. 2, a cylindrical cooling water passage 81 is formed inside the cooling roll 8. The cooling water supplied from an inlet 83 formed on one end side of a rotating shaft 82 of the cooling roll 8 spreads radially along a communicating passage 84, is introduced into one end of the cooling water passage 81, flows along the axial direction of the cooling roll 8, and then joins with the other end of the cooling water passage 81 and is discharged from an outlet 85 formed on the other end side of the rotating shaft 82.
[0046] A radial thickness T from the surface of the chill roll 8 to the cooling water passage 81 is 5 mm or more and less than 25 mm. If the thickness T is less than 5 mm, the chill roll 8 is easily deformed by centrifugal force caused by the rotation of the chill roll 8, and there is a risk that the surface (outer circumferential surface) of the chill roll 8 and the tip of the nozzle 6 may come into contact with each other. On the other hand, if the thickness of the chill roll 8 is 25 mm or more, the heat capacity of the chill roll 8 increases, and the heat removal effect of the molten alloy by the cooling water decreases, so that the quenching speed of the molten alloy decreases, and the α-Fe crystal phase having an average crystal grain size of 100 nm or more oriented in the (200) direction, which is precipitated by heterogeneous nucleation during quenching and solidification, may exceed 10.0 vol % in the vicinity of the quench roll surface or free surface of the Fe-Si-B-based iron-based soft magnetic alloy ribbon, and therefore low iron loss at the same level as that of the Fe-Si-B-based amorphous alloy cannot be maintained. The thickness T is preferably 5 mm or more and less than 23 mm, and considering the balance between the strength and heat extraction capacity of the cooling roll 8, it is more preferably 7 mm or more and less than 20 mm.
[0047] The amount of cooling water flowing inside the cooling roll 8 is 0.1 m 3 / min or more 20m 3 / min. The amount of cooling water is less than 0.1 m 3 If the rate is less than 20 m / min, the molten metal supplied to the surface of the chill roll 8 from the nozzle 6 cannot be sufficiently removed, the surface temperature of the chill roll 8 rises, the roll surface melts locally, the Fe-Si-B iron-based soft magnetic alloy ribbon sticks to the chill roll surface, and the molten metal cannot be quenched continuously. 3 If the flow rate exceeds 0.3 m / min, water leakage is likely to occur from the rotary joint for supplying cooling water to the inside of the chill roll 8, and quenching of the molten metal may not be continued. 3 / min or more 15m 3 / min or less is preferable, and 0.4m 3 / min or more 10m 3 / min or less is more preferable.
[0048] In order to ensure a stable quenching rate from when the molten alloy is ejected onto the surface of the chill roll 8 until it is peeled off, the temperature of the cooling water is set to be equal to or higher than 5° C. and lower than 60° C. In order to prevent condensation on the chill roll 8, the temperature of the cooling water is preferably equal to or higher than room temperature (e.g., equal to or higher than 23° C. and lower than 30° C.) and lower than 60° C.
[0049] [Heat treatment] The method for producing the iron-based soft magnetic alloy of the present invention may further include a heat treatment step in which the ribbon-shaped rapidly solidified alloy obtained by the rapidly solidifying step is heat-treated at a constant temperature of 180°C to 450°C. This makes it possible to remove distortion caused in the iron-based soft magnetic alloy powder due to stress during pulverization, and further improves the magnetic permeability. If the heat treatment temperature is less than 180°C, the effect of removing distortion is reduced, while if it exceeds 450°C, the iron loss tends to increase due to the crystal grain growth of α-Fe constituting the iron-based soft magnetic alloy. The heat treatment temperature is preferably 200°C to 400°C, more preferably 200°C to 350°C. The heat treatment is preferably performed in a vacuum or inert gas atmosphere, but heat treatment in the air is also acceptable as long as it is 350°C or less.
[0050] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.
[0051] 100 kg of raw materials containing B, C, Co, and Fe with a purity of 99.5% or more were placed in an alumina crucible (melting furnace) and melted by high-frequency induction heating to form a molten alloy, so as to obtain the alloy compositions shown in Examples 1-8 and Comparative Examples 9-12 in Table 1 below. 50 kg of this molten alloy was poured into an alumina storage vessel with an inner diameter of 200 mm and a height of 400 mm and a single slit nozzle made of BN at the bottom. The slit width and length of the nozzle are as shown in Table 1.
[0052] Then, 50 kg of the molten alloy was further heated by passing electricity through a high-frequency heating coil installed around the molten alloy storage vessel, and after the temperature of the molten alloy reached a temperature of about 100°C higher than the melting point of the alloy composition, the alumina molten alloy stopper arranged on the top of the nozzle was pulled out, and the molten alloy was sprayed from the nozzle onto the surface of the chill roll directly below. The chill roll was made of chrome zirconium copper, and the outer diameter and thickness of the chill roll, as well as the gap between the nozzle and the chill roll surface, are as shown in Table 1. The spray pressure of the molten alloy from the nozzle, the roll surface speed of the chill roll, the thickness of the chill roll (the radial distance from the roll surface to the cooling water channel), the amount of roll cooling water, the temperature of the roll cooling water, and the arithmetic mean roughness (Ra) of the roll surface of the chill roll are as shown in Table 2.
[0053] The molten alloy sprayed onto the surface of the chill roll formed a puddle on the surface of the chill roll and was rapidly solidified at the interface between the puddle and the chill roll, obtaining a ribbon-shaped Fe-Si-B rapidly solidified alloy having the average thickness and width shown in Table 3.
[0054] The structure of the obtained Fe-Si-B rapidly solidified alloy was evaluated by powder X-ray diffraction (XRD), and it was found that the iron-based soft magnetic alloys of Examples 1 to 8 all had a metal structure in which the α-Fe phase was isotropically precipitated without being oriented in a specific direction. The volume ratio of the amorphous phase calculated from the powder X-ray diffraction results is shown in Table 3.
[0055] As representative examples, powder X-ray diffraction profiles of Example 3 and Example 6 are shown in Figures 3 and 4, respectively. In both Figures 3 and 4, the main peak of α-Fe (110) and the secondary peak (200) were confirmed, and since both were diffraction peaks with wide half-value widths, it was confirmed that the metal structure was a fine metal structure consisting of an isotropically precipitated α-Fe crystal phase. A transmission electron microscope (TEM) photograph of Example 3 is shown in Figure 7. The metal structure of Example 3 shown in Figure 7 was an extremely fine metal structure with an average crystal grain size of 1 nm or less.
[0056] The results of measuring the saturation magnetic flux density Bs, the core loss (core loss) and magnetic permeability (μ) at a magnetic flux density of 1.5 T at 2 kHz, and the core loss at a magnetic flux density of 1.5 T at 20 kHz for the rapidly solidified alloys of Examples 1-8 are shown in Table 4. The measurement of Bs was performed using a vibration type sample magnetometer manufactured by Toei Kogyo Co., Ltd., and the measurement of μ and core loss was performed using an Iwasaki Electric Co., Ltd. BH analyzer equipped with an SST unit (single sheet magnetic property tester).
[0057] On the other hand, the rapidly solidified alloys of Comparative Examples 9 and 12 were evaluated by powder X-ray diffraction (XRD) to show a diffraction peak with α-Fe (200) as the main peak, and it was found that the alloys had a crystalline structure containing coarse α-Fe that was in-plane oriented in the rapidly solidified alloy ribbon due to heterogeneous nucleation caused by insufficient quenching of the molten metal. As representative examples, the powder X-ray diffraction profiles of the rapidly solidified alloy ribbons of Comparative Example 9 and Comparative Example 12 are shown in Figures 5 and 6, respectively. The volume ratios of the amorphous phase calculated from the powder X-ray diffraction results are as shown in Table 3. Comparative Examples 10 and 11 could not form rapidly solidified alloy ribbons.
[0058] As with Examples 1-8, for Comparative Examples 9 and 12, the saturation magnetic flux density Bs, the core loss (core loss) and magnetic permeability (μ) at a magnetic flux density of 1.5 T at 2 kHz, and the core loss at a magnetic flux density of 1.5 T at 20 kHz were measured. The results are shown in Table 4.
[0059] [Table 1]
[0060] [Table 2]
[0061] [Table 3]
[0062] [Table 4] [Explanation of symbols]
[0063] l Single roll molten metal quenching device 2 Melting furnace 3 Molten alloy 4 Tilt axis 5. Hot water container 1. Water outlet nozzle 7 Slit 8. Cooling roll 9 Rapidly solidified alloys
Claims
1. Composition formula (Fe 1-m Co m ) 100-x-y S x (B 1-n C n ) y where the composition ratios x, y, m, and n are expressed as follows: 1.0≦x≦3.0 atomic%, 11.0≦y≦14.0 atomic%, 0.05≦m≦0.5、 0.0≦n≦0.3 preparing a molten alloy having a composition that satisfies the above; and a rapid solidification step of rapidly solidifying the molten alloy sprayed from the nozzle onto a cooling roll made mainly of any one of pure copper, a copper alloy, Mo, and W. The cooling roll has an outer diameter of 300 mm or more and 2000 mm or less, has a cylindrical cooling water passage formed therein through which cooling water flows in the axial direction, has an arithmetic mean roughness (Ra) of the surface of 0.01 μm or more and 0.6 μm or less, and has a radial thickness from the surface to the cooling water passage of 5 mm or more and less than 25 mm, The rapid solidification step is performed by using 0.1 m of cooling water having a temperature of 5°C or higher and lower than 60°C. 3 / min or more 20m 3 a flow rate of less than 1 / min of water is passed through the chill roll, the chill roll is rotated at a roll surface speed of 15 m / sec to 50 m / sec, and the molten alloy is sprayed from the nozzle onto the surface of the chill roll to form a thin ribbon of rapidly solidified alloy having a thickness of 18 μm to 40 μm and consisting of ultrafine α-Fe as the main phase and an average crystal grain size of 1 nm or less.
2. 2. The method for producing an iron-based soft magnetic alloy according to claim 1, wherein the nozzle is made of a material mainly composed of any one of quartz (SiO2), boron nitride (BN), silicon carbide (SiC) and alumina (Al2O3), and sprays the molten alloy at a pressure of 5 kPa or more and 50 kPa or less.
3. the nozzle is a single slit nozzle, and is arranged so that a longitudinal direction of the slit is perpendicular to a rotation direction of the cooling roll; The opening width of the slit is 0.2 mm or more and 0.8 mm or less, 3. The method for producing an iron-based soft magnetic alloy according to claim 2, wherein the distance from the nozzle to the chill roll is 0.1 mm or more and 2.0 mm or less.
Citation Information
Patent Citations
Production of metal strip and nozzle for production
JP1988220950A
Production of thin strip of amorphous alloy having large thickness
JP1993329587A
Ferrous amorphous alloy
JP1995113151A
Multilayered magnetic alloy thin strap
JP1996124731A
Amorphous alloy ribbon
JP2017035737A
Cited By
Iron-based soft magnetic alloy and its manufacturing method
JP7765140B1